EMILIN-1 Deficiency Induces Elastogenesis and Vascular Cell Defects - Zanetti, Miriam (American Society for Microbiology, 2004)
EMILINs constitute a family of genes of the extracellular matrix with high structural similarity. Four genes have been identified so far in human and mouse. To gain insight into the function of this gene family, EMILIN-1 has been inactivated in the mouse by gene targeting. The homozygous animals were fertile and did not show obvious abnormalities. However, histological and ultrastructural examination revealed alterations of elastic fibers in aorta and skin. Formation of elastic fibers by mutant embryonic fibroblasts in culture was also abnormal. Additional alterations were observed in cell morphology and anchorage of endothelial and smooth muscle cells to elastic lamellae. Considering that EMILIN-1 is adhesive for cells and that the protein binds to elastin and fibulin-5, EMILIN-1 may regulate elastogenesis and vascular cell maintenance by stabilizing molecular interactions between elastic fiber components and by endowing elastic fibers with specific cell adhesion properties.